Nutrition and management strategies for confinement fed cattle: step-up programs, alternative feed ingredients, and health programs - Wallace, Justin Oliver (Kansas State University, 2008)
Three experiments were conducted to examine nutritional and management strategies for different segments of the beef industry. The first experiment examined the effects of feeding traditional step-up diets (STEP) vs. limit-feeding (LIMIT) the finishing diet to adapt cattle to high-concentrate diets. When all cattle reached ad libitum intake of the finishing diet there was a trend (P = 0.09) for DMI to be different between treatments. During week 1, STEP cattle had higher total VFA concentrations (P = 0.02), while LIMIT cattle had higher valerate absorption (P = 0.02) and disappearance (P = 0.08). During week 4, LIMIT cattle had higher total VFA concentrations (P = 0.03) and lower valerate disappearance and absorption (P = 0.05) than STEP cattle. These results indicate that limit-feeding the finishing diet may inhibit nutrient absorption from the rumen or this method may cause increased production of valerate by lactate utilizing bacteria due to a more acidotic rumen environment. The second experiment examined the effects of feeding 5% (DM basis) dried, full-fat corn germ (GERM) on feedlot performance and carcass characteristics of naturally raised yearling steers and heifers. Carcass-adjusted ADG was higher for GERM cattle (P = 0.04). There were no other differences in performance or carcass characteristics. Total incidence of liver abscesses and the incidence of severe liver abscesses were decreased by 12 and 8.2% (P = 0.01 and 0.02, respectively) when GERM was added to the diet. Corn germ can be added to finishing diets at 5% without affecting performance and carcass characteristics. Producers raising natural cattle may also be able to benefit from the reduced incidence of liver abscesses. The third experiment examined concurrent metaphylactic treatment of high-risk calves with tulathromycin and chlortetracycline. Calves were placed on 1 of 3 treatments: 1) no top-dress pellets; 2) diet top-dressed with pellets containing chlortetracycline; or 3) diet top-dressed with pellets containing no chlortetracycline. There were no differences in the performance or health of these calves (P > 0.25). There are no additive benefits of concurrent metaphylaxis using both tulathromycin and chlortetracycline. This information could assist producers when designing receiving health protocols for high-risk calves.
Keywords: Metaphylaxis; Limit-feeding; Adaptation; Naturally raised cattle; Corn germ; Chlortetracycline; Agriculture, Animal Culture and Nutrition (0475)